1983
DOI: 10.1104/pp.71.2.432
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid Accumulation in Cotton Leaves in Response to Dehydration at High Pressure

Abstract: Pressure-volume techniques were utilized to examine the control of abscisic acid (ABA) accumulation in dehydrated cotton (Gossypium hirsutum L. cv Tamcot SP 37) leaves. Leaves were rapidly dehydrated in a pressure chamber to a balance pressure coincident with the loss of cellular turgor, and then the pressure was either maintained at that level or released. Rapid accumulation of ABA began within two hours after the balance pressure was achieved, whether or not the high pressure potential of the cells was maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 14 publications
0
14
1
Order By: Relevance
“…corresponding to a decline in RWC or volume, independently of C P . An important control showed that pressurizing leaves entirely enclosed within the pressure chamber-without the petiole protruding and thus without leaf water lossonly led to minimal stimulation of ABA accumulation, indicating that increases in C P alone were not the stimulus (Ackerson and Radin, 1983). This same approach was revived in recent articles Sussmilch et al, 2017), though these authors argued that the application of external pressure would reduce leaf turgor and that this reduction of turgor triggered ABA accumulation.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…corresponding to a decline in RWC or volume, independently of C P . An important control showed that pressurizing leaves entirely enclosed within the pressure chamber-without the petiole protruding and thus without leaf water lossonly led to minimal stimulation of ABA accumulation, indicating that increases in C P alone were not the stimulus (Ackerson and Radin, 1983). This same approach was revived in recent articles Sussmilch et al, 2017), though these authors argued that the application of external pressure would reduce leaf turgor and that this reduction of turgor triggered ABA accumulation.…”
mentioning
confidence: 95%
“…When cotton (Gossypium hirsutum) or maize leaves were dehydrated under sustained pressure in a pressure chamber, such that the leaves lost water by extrusion through the petiole, ABA accumulated (Ackerson and Radin, 1983;Jia et al, 2001). The authors argued that pressurizing the leaves during dehydration maintained cell turgor, and thus that ABA accumulation was driven instead by cellular volume shrinkage or relaxation of the cell wall, i.e.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Summary of evidence for and against the declines in leaf water potential (C leaf ), turgor potential (C P ), solute potential (C S ), or RWC or cell volume as drivers of ABA accumulation in previous studies, and whether the putative driver is supported as important for ABA accumulation in studies using externally applied pressure, as analyzed in Table I). c Ackerson and Radin (1983); Jia et al (2001).…”
Section: Speciesmentioning
confidence: 99%